Claude Debussy [compact disc] - Debussy, Claude, 1862-1918 (Deutsche Grammophon, 2018)
Maestro Barenboim is one of the most important artists and humanists of our times, whose commitment and contribution to music, education, politics and main concerns of our society enrich and inspire us all. 2018 sees a range of releases, starting off with a personal collection of the maestro to celebrate the Debussy 100th anniversary year.